2020
DOI: 10.1177/2280800020936540
|View full text |Cite
|
Sign up to set email alerts
|

Sol–gel-entrapped pH indicator for monitoring pH variations in cementitious materials

Abstract: Sensors for pH evaluation of concrete were made by a sol–gel process with alizarin yellow as pH indicator. The optical absorbance was measured with a visible spectrophotometer coupled with optical fibers. Results showed that the sensors had good reversibility, reproducibility, and fast response time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 56 publications
0
8
0
Order By: Relevance
“…Srinivasan et al used a sol-gel/TNBS (trinitrobenzenesulfonic acid) composite that showed a variation in color in the pH range from 12 to 14 [ 61 ]. Finally, Inserra et al [ 62 ] developed an optical pH probe with a pH-sensitive dye embedded in a silica monolith made by a sol-gel method. Alizarin yellow, which changes color from yellow to red when the pH ranges from 10 to 12, was used for this purpose.…”
Section: Sensors To Evaluate the Carbonation Of Concretementioning
confidence: 99%
“…Srinivasan et al used a sol-gel/TNBS (trinitrobenzenesulfonic acid) composite that showed a variation in color in the pH range from 12 to 14 [ 61 ]. Finally, Inserra et al [ 62 ] developed an optical pH probe with a pH-sensitive dye embedded in a silica monolith made by a sol-gel method. Alizarin yellow, which changes color from yellow to red when the pH ranges from 10 to 12, was used for this purpose.…”
Section: Sensors To Evaluate the Carbonation Of Concretementioning
confidence: 99%
“…The development of OFS has expanded in recent years, favoring advances in different areas such as telecommunications [17,18], materials chemistry [19,20], microelectronics [21][22][23], and nanotechnology [24][25][26]. Focusing on the area of chemistry, most of the existing OFS are based on transduction principles such as fluorescence [27][28][29][30] or absorbance [31,32]. In the mentioned cases, the analytical response is achieved by changing the optical properties of a fixed recognition agent on a solid support due to the interaction with the species to be determined.…”
Section: Fundamentalsmentioning
confidence: 99%
“…Chemosensors use molecular recognition mechanism for recognition of an analyte, allowing the occurrence of the signal transduction. The signal produced may be based on the principles of fluorescence [32] or absorbance [33]. These types of molecules add to the OIH membrane's extra optical and electrical properties.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Jin et al [24] developed a pH potentiometer applicable to teaching in a chemistry laboratory setting. Moreover, a pH sensor to assess the changes in cementitious materials, through a sol-gel process with an alizarin yellow as meter, has been developed [25]. Additionally, portable chemical sensors, requiring specialized processes for manufacturing, have been reported for non-invasive real-time monitoring of parameters for medical care and disease diagnosis [26,27].…”
Section: Introductionmentioning
confidence: 99%